AFCRL infrared sky survey: Volume I. Catalog of observations at 4, 11, and 20 microns - Walker, Russell G.; Price, Stephan D.; Air Force Cambridge Research Laboratories (U.S.) (Air Force Cambridge Research Laboratories, Air Force Systems Command, United States Air Force, 1975)
A survey of the sky in the intermediate infrared spectral region is reported. The objective was to obtain the brightness and spatial distribution of a representative sample of the types of celestial objects that emit strongly in the infrared. Of primary concern was the determination of the positions of unusual sources of emission with sufficient accuracy to enable them to be acquired by ground based telescopes for further detailed investigation.
"Optical Physics Laboratory Project 7670."
"ADA016397 (from http://www.dtic.mil)."
"14 July 1975."
Includes bibliographical references (pages 153-158).
v. l. Catalog of observations at 4, 11, and 20 microns.
Keywords: Infrared sources / Observations / Catalogs.; Infrared astronomy / Observations.